Potential differences between Leptospira serovars, host‐adapted (Bratislava) and incidental (Copenhageni), in determining reproductive disorders in embryo transfer recipient mares in Brazil. (24th May 2014) - Pinna, A.; Martins, G.; Hamond, C.; Medeiros, M. A.; de Souza, G. N.; Lilenbaum, W.
Abstract : The objective was to investigate potential differences between two Leptospira serovars, host‐adapted (Bratislava) and incidental (Copenhageni), in causing reproductive disorders in mares. From August 2009 to March 2011, 608 adult recipient mares from eight studs located in the state of Rio de Janeiro, Brazil, were screened for leptospirosis. These mares were 3–8 years of age, of various breeds, and were managed in a semiextensive system (embryo transfer centres). According to the reproductive history of these mares, the studs were categorised as Group A (357 mares: high prevalence of reproductive problems), and Group B (251 mares: all pregnant). Of the 608 samples tested serologically, 273 (44.9 per cent) were reactive (titres ≥200), predominantly against Bratislava (62.3 per cent of reactive mares). In Group A, 247/357 sera (69.2 per cent) were reactive, with reactivity against Bratislava (64.8 per cent of reactive). By contrast, in Group B, only 26/251 sera (10.4 per cent) were reactive, the majority against Copenhageni (61.5 per cent of reactive). Seroreactivity against Bratislava was more likely to be associated (P<0.001) with reproductive problems than seroreactivity against Copenhageni; this association was true for early embryonic death (P<0.001), perinatal death (P<0.01), and abortion (P<0.001). Additionally, 29 urine samples were collected (from Group A mares) for Leptospira species PCR, of which 16 were positive (55.2 per cent). We concluded that leptospirosis was associated with poor reproductive performance in embryo recipients, with the majority due to host‐adapted Bratislava.